Pendidikan Politik Berbasis Digital bagi Pemuda Karang Taruna Melalui Pelatihan Pembuatan Konten Digital - Faiz Albar Nasution; Muhammad Husni Thamrin; Lydia Nurhasanah Nasution; Imam Fahreza (Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
Every General Election, the citizens of Medan City face quite a challenge in exercising their right to vote. Lack of political understanding may be the cause of the low voter participation among the citizens of Medan City. Passive activities in political education and political socialization contributed to the low level of involvement in Medan City. Therefore, the purpose of this service is to inform youth groups about digital-based political education through digital content development training. Participatory Learning and Action methods through learning procedures that combine lecture techniques and participatory discussions to group learning are carried out in this activity. Service activities carried out for Youth Karang Taruna, Medan Johor Subdistrict, include: First, learning about political education. Second, improve digital literacy competence and digital content creation. Third, training to become a content creator. The results of the service recommend activity participants improve their skills in creating digital content. Further development and training are needed to be skilled in honing the ability to produce digital content. For the sake of knowledge that is implemented in the form of digital-based political education, continuous guidance and assistance are needed for Youth Karang Taruna, Medan Johor District.